Tempos na formação docente: entre o identitário e o imaginário - Silva, Monique da (2013)
This masters' dissertation is inserted in the Post-graduate Program in Education, of Federal University of Santa Maria, integrating the Research Line 1: Formation, Knowledgement and Professional Development. This study aimed to investigate the relationship among Time, and Imaginary Social instituted about the same, and teaching, especially teacher formation, in contemporaneity. The methodology of the research occurred in two major moments: bibliographic studies about the subject; and empirical research conducted with teachers in the public schools of the city of Santa Maria. In order to explain theoretically the possible relations, it was needed a study of the theories that some philosophers have developed about time, including Aristotle, Augustine, Gaston Bachelard, Gilbert Durand and Cornelius Castoriadis, morover, when we talk about teaching, we departed of Gilles Ferry. Also, through narratives written in daily life by collaborating, it was possible to make an interlacement between teaching and influences of imaginary imposed on the time of the daily lives of teachers. In this scenario, with the development of research, it was realized through the writings about memory, teacher formation, time, teaching and self care, that time established in the profession is not always the tiredness. Quite the contrary, this work shows that teachers that place themselves open to experiences of continuing education, and cultivate self-care in their routines, beyond the barrier established of teacher malaise, presenting theyr good relationship with time as a fundamental factor of good relationship with the teacher.